AB042. Sarcoidosis or Berylliosis? Two diseases with similar histologic findings - Cheva, Angeliki (Ann Transl Med, 2016)
BACKGROUND: The case of a male patient, 71, who presented with bilateral pleural effusion and previously unknown mediastinal lymphadenopathy. METHODS: Resection of three left-sided paratracheal lymph nodes was performed, 0.6–1 cm in greatest diameter. The tissue material was embedded in paraffin and stained with hematoxylin-eosin. RESULTS: Two out of the three lymph nodes demonstrated a destruction of their structure, due to the presence of abundant epithelioid, non-caseating granulomas within a collagenous/sclerotic stroma. The granulomas consisted of plenty of epithelioid histiocytes and multinucleated Langhans giant-cells. Schaumann bodies and asteroid bodies were recognised. Given the above, the diagnosis was that of a granulomatous inflammatory disease, like a sarcoidosis or berylliosis. After gathering a precise patient medical history, it was revealed that he had been working for many years in fertilizer manufacturing, with chronic exposure to beryllium. CONCLUSIONS: Sarcoidosis is usually a diagnosis of exclusion, as there are no pathognomonic clinical features or diagnostic examinations. When pleural effusion is the first manifestation of the disease, clinical estimation is usually oriented to other diseases. Cases have been reported, in which the patient was misdiagnosed (e.g., with tuberculosis) and mistreated for several months, before sarcoidosis is diagnosed. The microscopic examination of mediastinal lymph nodes contributes to this diagnostic challenge, with a low complications risk. Sarcoidosis and berylliosis have similar clinical, imaging and histologic findings. Typical are the epithelioid, non-caseating granulomas. Schaumann bodies are found in 70% of sarcoidosis and asteroid bodies are more unusual, found in 2–9% of the cases. For the definite differential diagnosis between these entities, a detailed medical history of the patient is necessary, while the Beryllium Lymphocyte Proliferation Test (BeLPT) is also available.